(3GdeSGFd GdYTQhfs
(3ChdgG (B:s
(3Ef GdEjLGH hGdSdH bO jYQaGf ef ZjQ CNP GdbVjI hGdebOeI ai MOjgeG UGQ cd hGMO efgeG bVjI hdjS Pdc gh Gdbhd s
(3BNQgG (B:s
(3hYOOfG LejY GdbVGjG GdTQWjI adjaYd Pdc GdeOYhf ddUfGYI ef Cgd GdOgQ hdjbGHd cd Hcd hGdSdGe BNQ GdeSGFd s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs